Efficacy of postoperative adjuvant hepatic artery infusion chemotherapy for hepatocellular carcinoma in microvascular invasion: a propensity-matched score - Feng, Xu; Wu, Xinhua; Chen, Kai; Ao, Yupei; Shi, Zhengrong; Gong, Yixuan (Frontiers in Surgery, 2025)
BackgroundPatients with hepatocellular carcinoma (HCC) and microvascular invasion (MVI) still have high rates of recurrence and poor survival outcomes after radical resection. This study aims to investigate the effect of postoperative adjuvant hepatic arterial infusion chemotherapy (PA-HAIC) on the recurrence of HCC patients with MVI after radical liver resection (LR).Materials and methodsThis study retrospectively evaluated patients with HCC who underwent LR with MVI at the Hepatobiliary Surgery Department of the First Affiliated Hospital of Chongqing Medical University from 1 January 2020 to 30 June 2024. The recurrence-free survival (RFS) of patients who received PA-HAIC was compared with that of patients who only received LR by propensity score- matching (PSM), and subgroup analyses were performed to compare the efficacy of PA-HAIC for patients in different subgroups based on patient combined risk factors for recurrence, patients' age and the number of PA-HAIC treatments received.ResultsA total of 175 HCC patients with MVI who underwent LR were enrolled in this study, including a total of 72 patients in the PA-HAIC group and 103 patients in the LR group, and after PSM, 67 patients were matched in the PA-HAIC and LR groups, respectively. In the entire cohort, the median RFS (mRFS) were 33.00 months (95% CI, 29.32–36.68 months) and 15.00 months (95% CI, 11.58–18.51 months) for patients in the PA-HAIC and LR groups, respectively (p < 0.001). In the PSM cohort, the mRFS was 33.00 months (95% CI, 28.74–37.26 months) and 18.00 months (95% CI, 16.25–19.75 months) for patients in the PA-HAIC and LR groups, respectively (p < 0.001). When stratifying patients based on combined risk factors in the entire cohort, in cases where MVI + tumor diameter ≥5 cm (MVID), MVI + multiple tumor (MVIN), and MVI + tumor diameter ≥5 cm + multiple tumor (MVID + N), patients in the PA-HAIC group showed better mRFS than those in the LR group. Within the PA-HAIC group, there was no statistically significant difference in mRFS among patients with MVI alone, MVID, MVIN, and MVID + N. The conclusions of the PSM cohort are consistent. Furthermore, in patients aged ≤55 years, PA-HAIC significantly improved patient mRFS (PA-HAIC group: 32.00 months, 95% CI: 27.61–36.39 months vs. LR group: 13.00 months, 95% CI: 6.48–19.52 months, p < 0.001). In addition, patients who received two PA-HAIC treatments had significantly better mRFS compared to those who received only one PA-HAIC treatment (36.00 months, 95% CI 28.26–43.74 months vs. 31.00 months, 95% CI 21.34–40.66 months, p = 0.045). Also, the mRFS of patients who received three or more PA-HAIC treatments was similar to that of patients who received two HAIC treatments (p = 0.707).ConclusionsPA-HAIC is beneficial for HCC patients with MVI after radical liver resection, and patients aged ≤55 years with MVI + tumor diameter ≥5 cm, MVI + multiple tumors or MVI + tumor diameter ≥5 cm + multiple tumors should receive at least two PA-HAIC treatments.